Optimisation of the synthesis of Mg-AI-CO3 LDH and the partial substitution of Mg/Ca-based LDHS - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 2014.